Identification of the main components in the implementation of the referral system in the health and treatment system of Bojnord city - Alireza Barati; Majid Mirmohammadkhani; samaneh Ghads; Esmaeil Moshiri (Tehran University of Medical Sciences, 2022)
Introduction: The present study qualitatively investigated the main components that should be considered for the implementation of the referral system in Bojnord city. Methods: In this study, data were collected through doing interviews with experts, and finally, the importance of all the extracted components was evaluated using a researcher-made questionnaire. Also, the exploratory factor analysis method was used to classify the components in main sets. Kolmogorov-Smirnov, one-sample t-test, performed in Excel and SPSS software, was used for statistical analysis. Results: The most frequent noted components by the experts included "empowerment (knowledge, skill, psychological) of human resources involved in the referral system", "paying attention to the motivation of human resources involved in the referral system", and "developing suitable processes for the referral system and re-engineering the processes to meet the conditions". Finally, the main requirements in the referral system of Bojnord city were divided into three categories included organizational and management, manpower, and technology-based requirements. Conclusion: Briefly, some components may lead to improvement of the referral system, which can be categorized into organizational and management, manpower, and technology-based requirements. Detailed planning to improve the referral system can lead to the improvement of the health system.